1976
DOI: 10.1093/clinchem/22.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase isoenzyme patterns in human tissue obtained at surgery.

Abstract: Chromatography on DEAE-Sephadex A-50 was applied to study the quantitative distribution of creatine kinase isoenzymes in extracts of human tissue obtained during surgery. The results are compared with those determined by an immunological method [Clin. Chim. Acta 58, 223 (1975)]. Conflicting results for some organs as reported by the two methods are probably attributable to postmortem autolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
10

Year Published

1978
1978
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(35 citation statements)
references
References 1 publication
0
25
0
10
Order By: Relevance
“…It has been reported that M-CK constitutes 35 % of total CK activity in the postmortem human brain (Hamburg et al, 1990). However, human brain extracts obtained directly at surgery did not contain significant amounts of M-CK (Tsung, 1976), and other human brain extracts contained specific CK activities which were 30-fold higher than those reported from Hamburg and coworkers (Tsung, 1976;McBride and Rodgerson, 1984). Thus, it seems likely that the figure reported by Hamburg et al (1990) was overestimated due to postmortem artefacts.…”
Section: Isoenzyme-specific Localization Of Creatine Kinase Isoenzymementioning
confidence: 65%
“…It has been reported that M-CK constitutes 35 % of total CK activity in the postmortem human brain (Hamburg et al, 1990). However, human brain extracts obtained directly at surgery did not contain significant amounts of M-CK (Tsung, 1976), and other human brain extracts contained specific CK activities which were 30-fold higher than those reported from Hamburg and coworkers (Tsung, 1976;McBride and Rodgerson, 1984). Thus, it seems likely that the figure reported by Hamburg et al (1990) was overestimated due to postmortem artefacts.…”
Section: Isoenzyme-specific Localization Of Creatine Kinase Isoenzymementioning
confidence: 65%
“…When corrections for the differences in working temperature are considered, the CK activities observed are, with one exception (Ogunro et al .. 1977), higher than any other reported in the literature (Tables I and III). Generally, neither sex nor age of the subjects are indicated in various papers dealing with this topic (Kleine, 1967;Lujf, 1973;Neumeier et al .• 1977;Ogunro et al .• 1977;Sobel et al .. 1977;Tsung, 1976). Unsatisfactory information is furnished as to the origin of the samples (e.g., "heart muscle") (lockers-Wretou and Pfleiderer, 1975;Lujf, 1973;Miyoshi et al .. 1975;Neumeier et al .. 1977;Ogunro et al .• 1977).…”
Section: Comparison With Data From Other Investigatorsmentioning
confidence: 99%
“…For instance, with regard to CK, activities of approximately 80-2,100 U/g wet weight have been reported. Other critical aspects concerning the published material are the use of samples obtained at variable times postmortem (Jockers-Wretou and Pfleiderer, 1975;Kleine, 1967;Miyoshi et al .• 1975), the application of various extraction and analysis procedures which may not be optimal (Jockers-Wretou and Pfleiderer, 1975;Kleine, 1967), as well as the small number of cases studied (Lujf, 1973;Tsung, 1976). Furthermore, in many papers the working temperature is not indicated, and in others it is variable (25, 30, or 37°C) (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…As for the BB isoenzyme, the brain contains large amounts. Other tissues also rich in the BB dimer are the prostate, lung, urinary bladder, uterus, thyroid, pancreas, stomach, intestine, and kidney [2].…”
mentioning
confidence: 99%